2011
DOI: 10.1159/000326952
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Cervical Sarcoidosis Identified on Pap Test: Cytomorphologic Findings and Differential Diagnosis

Abstract: Background: Sarcoidosis is a multisystem inflammatory disease of uncertain etiology that is histopathologically characterized by non-necrotizing granulomas. It typically involves the lungs and lymph nodes, but has been reported in many other organ systems as well. Sarcoidosis involving the female genital tract, the uterus in particular, is a rare event with isolated accounts in the medical literature. Case: We present a rare occurrence of cervical sarcoidosis in a Pap test of a 31-year-old woman with a history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Other granulomatous diseases of the cervix should be considered, such as amoebiasis, 27 schistosomiasis, 28 sarcoidosis, 29 and history of prior biopsy and surgery 30 should be considered in differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other granulomatous diseases of the cervix should be considered, such as amoebiasis, 27 schistosomiasis, 28 sarcoidosis, 29 and history of prior biopsy and surgery 30 should be considered in differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Like any other extra pulmonary manifestation of sarcoidosis, most of the patients have concomitant pulmonary involvement and the disease seems to occur more frequently in the Black population. A majority of the patients present with menstrual irregularities; menorrhagia, metrorrhagia, and postmenopausal bleeding are more commonly reported symptoms than amenorrhea [6, 817]. Some of the patients were asymptomatic, and the diagnosis was made based on examination of the hysterectomy or autopsy specimens [6].…”
Section: Discussionmentioning
confidence: 99%
“…Some cases of uterine sarcoidosis presented with cervical erosions [8], endometrial polypoid lesions [18], and recurrent serometra [16]. Others were incidental findings on cervical pap smear [17] and patients who underwent surgery for uterine myomas. Endometrial curettage led to the diagnosis in the majority of the cases; in others the diagnosis was made on examination of the hysterectomy, polypectomy, and autopsy specimens [6, 17, 18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are only few data on this topic. Some studies have by biopsy shown that systemic diseases such as sarcoidosis or tuberculosis can affect the endometrial mucosa by causing granulomatous inflammation in the endometrial lining [51]. Another study by Kurganov [52] in rodents showed that the endometrial mucosa during and after a systemic infection/chronic inflammation was infiltrated by eosinophils and that the infiltrated endometrium was unable to incorporate the embryonated egg.…”
Section: Methodsmentioning
confidence: 99%